Loan loss provisions, Capital and Earnings Management: Evidence from German Banks - Ye, Yutong (2018)
German Commercial Code endows banks with discretion to build up loan loss provisions. In this dissertation, loan loss provision hypotheses including earnings and capital management are re-examined by specifying two kinds of models on a panel of German saving banks, cooperative banks and commercial banks for the period from 2011 through 2017. In static model, the study finds that: (1) German bank managers use discretionary loan loss provisions to smooth bank earnings (before provisions and tax), and to meet capital adequacy ratio as required by bank regulators；(2) Procyclical provisioning behaviour has been found even when the build-up of loan loss provisions in Germany are insignificantly related to the level of non-performing loans ; (3) Further analysis incorporating the interaction term between X-efficiency and earnings management in the model specification shows that more efficient banks are more sensitive to the change in earnings so that they need more loan loss provisions to reduce earnings volatility. However, results in a dynamic model only show robust evidence of earnings and capital management but little evidence of procyclicality or any interactive effect.